An empirical investigation of the relationships among spirituality, well-being, and psychological health - Zubairi, Az Athirah; Md Sawari, Siti Salwa (Edupedia Publications Pvt Ltd, 2018)
In this paper researchers will examine the relationship between spirituality, well-being, and the psychological health. The design used for the study is survey research design to explore the uniqueness population of interest, and for the standardization of measurement. This study is a quantitative in nature, whereby researcher used Spiritual Well-Being Scale (SWBS) (Paloutzian and Ellison, 1982) to assess the spiritual well-being of the participants. On the other hand, psychological health was measured by three different set of questionnaires; General Self-Efficacy (GSES), Rosernberg Self- Esteem (RSE) and Satisfaction with Life Scale (SWLS). Result in this study indicated that spiritual health is significantly associated with psychological health; self-efficacy, self-esteem and life satisfaction.